Answer:
he earns 69 dollars
Step-by-step explanation:
1st grade question now give brainliest 5 stars and heart
The account is $4,480 after 3 years with a 4% investment
Answer: (f-g)(2)=14
Step-by-step explanation:
(f – g) (-2) means the same as subtracting f(2) and g(2). Since we are given f(x) and g(x), we can use them to solve. There are two ways to solve. One is to find f(2) and g(2), and then subtract them. Another way is to do (f-g)(x), then plug in x=2. I will show both methods.
Method 1
f(2)=3(2)²+1 [exponent]
f(2)=3(4)+1 [multiply]
f(2)=12+1 [add]
f(2)=13
g(2)=1-(2) [subtract]
g(2)=-1
(f-g)(2)=13-(-1) [subtract f(2) and g(2)]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Method 2
(f-g)(x)=3x²+1-(1-x) [distribute -1]
(f-g)(x)=3x²+1-1+x [combine like terms]
(f-g)(x)=3x²+x
(f-g)(2)=3(2)²+2 [plug in x=2, exponent]
(f-g)(2)=3(4)+2 [multiply]
(f-g)(2)=12+2 [add]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Now, we know that (f-g)(2)=14. We confirmed this with both methods.
Answer:
To find the x-intercept of any equation, set the y-value to 0.
Step-by-step explanation:
Example:
y=1x+4
To find x-intercept:
0=1x+4
1. Subtract 4 from both sides
2. Divide both sides by 1
The x-intercept is -4
<h3>Given Equation:</h3>
x = 7 + 3y
or, x - 3y - 7 = 0 ........ (i)
5x + 6y = 14
or, 5x + 6y - 14 = 0 .........(ii)
<h3>To Find:</h3>
The value of x and y.
<h3>Solution:</h3>
By dividing eq. ii by 2, we get
5/2x + 3y - 7 = 0 ........ (iii)
By adding eq. i and eq. iii, we get
15/2x = 0
or, <u>x = 0</u> ........(iv)
By putting eq.(iv) in eq. (i), we get
0 - 3y - 7 = 0
or, -3y = 7
or, <u>y = </u><u>-</u><u>7/</u><u>3</u>
<h2>Answer: ( 0, -7/3 )</h2>
The value of x and y is 0 and -7/3 respectively.